"Socially Responsible Marketing" To, With, and For Impoverished Populations. (December 2022) - Santos, Nicholas J.C.
This is a commentary on the macro and normative-ethical definition of socially responsible marketing proposed byLaczniak and Shultz (2021) from the perspective of marketing in impoverished markets. It considers the three dimensions of "marketing to", "marketing with", and "marketing for" impoverished populations. While the definition proposed by Laczniak & Shultz is broad and all-encompassing, a major limitation is in the elaboration of social sustainability. As social and ecological sustainability is proposed as an essential element of the definition, the scant attention paid to social sustainability is a major lacuna in the definitional construct.